Effect of ectoparasite Ichthyophthirius multifiliis on the histopathology and gill and gut microbiota of goldfish (Carassius auratus) - Bu, Xialian; Peng, Xianqi; Huang, Lei; Zhao, Yu; Jiao, Jinbiao; Zhu, Jian; Chen, Jing; Huang, Xiaohong; Zheng, Aqin; Qu, Huantao; Yao, Jiayun (Frontiers in Veterinary Science, 2025)
IntroductionThe ectoparasite Ichthyophthirius multifiliis, is the pathogen of white spot disease in freshwater fish, which parasitizes on gills, fins, and skins of fish, causing tissue damage and death of host. However, whether it influences gill and gut microbiota is still unknow.MethodsIn this study, H&E staining was used to show the gill and gut histopathological characteristics of I. multifiliis-infected and uninfected goldfish (Carassius auratus). Meanwhile, 16S rRNA gene amplicon sequencing was conducted to analyze the difference of gill and gut microbiota between I. multifiliis-infected and uninfected goldfish.ResultsHistopathological examination revealed that I. multifiliis has induced significant damage to the gills of goldfish, characterized by lamellae fusion, cell hyperplasia, cell hyperaemia, inflammatory infiltration, necrosis and desquamation. 16S rRNA gene sequencing result showed that alpha and beta diversity of gill microbiota was significantly reduced in the I. multifiliis-infected group, while no significant changes were observed in gut microbiota. Genus Candidatus Megaira exhibited the highest relative abundance in the I. multifiliis-infected group. Meanwhile, the abundance of opportunistic pathogens Aeromonas and Achromobacter were increased in the intestines of I. multifiliis-infected goldfish.DiscussionThe increased presence of Candidatus Megaira may originate from within the cells of I. multifiliis. The increase of opportunistic pathogens Aeromonas and Achromobacter may pose a threat to the health of goldfish. In summary, this study laid a foundation for further research on the interaction between I. multifiliis and host microbiota.